Joint associations of PM10 and smoking with the risk of new-onset stroke in middle-aged and older adult Chinese adults: findings from the CHARLS cohort study - Chen, Shiqin; Lv, Tian; Li, Weiyu; Yu, Liang; Pan, Gonghua; Shen, Ting (Frontiers in Public Health, 2025)
BackgroundThe relationship between long-term exposure to particulate matter ≤ 10 μm in diameter (PM10), smoking, and stroke risk remains unclear. This study investigates their association.MethodsWe analyzed data from 10,839 participants in the 2013 wave of the China Health and Retirement Longitudinal Study (CHARLS). Long-term PM10 exposure was estimated using the China High Air Pollution (CHAP) dataset, and incident stroke cases were self-reported during follow-up through 2018. Multivariable Cox proportional hazards models, restricted cubic spline (RCS) analyses, and joint exposure models were employed.ResultsEach 1 μg/m3 increase in PM10 concentration was associated with a 0.3% higher risk of stroke (HR = 1.003; 95% CI: 1.000–1.005; p = 0.04). A nonlinear exposure–response relationship was observed (P for non-linearity = 0.04). Among PM10 exposure quartiles, only the third quartile (91.90–115.92 μg/m3) was significantly associated with increased stroke risk (HR = 1.36; 95% CI: 1.08–1.71; p < 0.01). Participants exposed to both high PM10 levels (≥91.9 μg/m3) and smoking had the highest stroke risk (HR = 1.72; 95% CI: 1.33–2.23; p < 0.01). No significant multiplicative or additive interaction between PM10 and smoking was found.ConclusionLong-term PM10 exposure and smoking are independent risk factors for stroke. The elevated risk observed within a specific concentration range of PM10 suggests a potential threshold or saturation effect. Individuals exposed to both risk factors are particularly vulnerable, highlighting the need for integrated public health strategies targeting both air quality improvement and smoking cessation.